Typological Structure of German Phraseology Outside Germany. Quantitative Parameters - Ostapovych, O. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The article deals with the modern theoretical concept in study of the variation of German phraseology abroad Germany. It is based on the synthesis of the theory of equal-righted pluricentrism with the new achievements of the cognitive linguistics. As a result the national state linguistic variant is considered as different from the regional, normatively non-codified and dialectal variation, a kind of cluster variant idiomatic thesaurus. The hypothesis of the structural isomorphy of the variant phraseology compared to the common German one has been empirically verified and vice versa - the hypothesis of the quantitative predominance in the Austrian phraseology of the structural model Adj+Sub under the Slavic linguistic influence has also been falsified